Biocontrol Agents of Phytonematodes. - Askary, T. H. (CABI, 2015)
Highlighting the use of biocontrol agents as an alternative to chemical pesticides in the management of plant parasitic nematodes, this book reviews the current progress and developments in the field. Tactful and successful exploitation of each biocontrol agent, i.e. nematophagous fungi, parasitic bacteria, predaceous mites, rhizobacteria, mycorrhiza and predaceous nematodes, has been described separately. The contributors are 23 eminent nematologists and their information has been compiled in 19 chapters.